Clinical distinctions of anti-topoisomerase positive limited cutaneous systemic sclerosis in early disease: results from the early Systemic sclerOsis Longitudinal Assessment Registry from Turkey - Yayla, Mücteba Enes; Okyar, Burak; Ersözlü, Emine Duygu; Özgür, Duygu Sevinç; Bes, Cemal; Çefle, Ayşe; Akdogan, Ali (Clinical and Experimental Rheumatology S.A.S., 2026)
Anti-topoisomerase I antibody (ATA) is typically associated with diffuse cutaneous systemic sclerosis (dcSSc). However, subset of limited cutaneous SSc (lcSSc) patients also present with ATA positivity. Emerging data suggest that ATA-positive lcSSc may represent a distinct or intermediate clinical phenotype. This study aimed to compare the demographic, clinical, and treatment features of early ATA-positive lcSSc patients with those of ACA-positive lcSSc and ATA-positive dcSSc patients. Patients were recruited from the multicentre Turkish SOLAR cohort (Systemic sclerOsis Longitudinal Assessment Registry). Among 295 SSc patients screened, 172 were included: 74 ACA-positive lcSSc, 55 ATA-positive lcSSc, and 43 ATA-positive dcSSc. Demographic, clinical, and treatment-related variables were analysed and compared across groups. ATA-positive lcSSc patients were younger at the onset of Raynaud's phenomenon (RP) (p=0.042), the first non-RP symptom (p=0.016), and at diagnosis (p=0.018) compared with ACA-positive lcSSc patients. Interstitial lung disease (ILD) was significantly more frequent in ATA-positive lcSSc (74.5%) than ACA-positive lcSSc (8.1%, p<0.001) and was comparable to ATA-positive dcSSc. Modified Rodnan skin scores were highest in ATA-positive dcSSc but were also significantly elevated in ATA-positive lcSSc (p<0.001). Pitting scars were more frequent in dcSSc. Among patients with ILD, ATA-positive lcSSc and ATA-positive dcSSc showed similar HRCT patterns. ATA-positive lcSSc patients were more frequently treated with glucocorticoids and mycophenolate mofetil than ACA-positive lcSSc, whereas cyclophosphamide was highest in dcSSc. ATA-positive lcSSc patients exhibit a clinically distinct phenotype characterized by a substantial risk of internal organ involvement, despite having less extensive skin disease. Their overlap with dcSSc and divergence from ACA-positive lcSSc highlight the importance of incorporating both skin involvement and serologic subtyping into the early management and risk stratification of SSc. © 2026, CLINICAL AND EXPERIMENTAL RHEUMATOLOGY. All rights reserved.
Keywords: Disease Subset; Interstitial Lung Disease; Mrss; Scleroderma